PENGARUH BIAYA PROMOSI DAN JUMLAH REKENING DPK TERHADAP JUMLAH DANA PIHAK KETIGA BPRS DI INDONESIA - Mochamad Indrajit Roy (Banque Syar'i : Jurnal llmiah Perbankan Syariah, 2020)
Promotional costs are one component that is expected to increase the total number of SRB DPK. The same is true with the amount of DPK accounts expected and suspected to be able to provide changes to the total number of SRB DPK. The author aims to analyze the alleged influence of Promotional Costs and Number of DPK Accounts on the Total Value of DPK in BPRS in Indonesia. Quantitative methods are used in this study. While the regression analysis is used to analyze the effect of promotion costs and the number of account deposits to the total amount of deposits in the SRB. The results showed that together the Promotion Cost and Number of DPK Accounts had a significant effect on the Total Number of DPK. Partially, Promotional Costs do not have a significant effect on Total Total DPK. Whereas the number of third party funds has a significant influence on the total number of third party funds.